The logistic experience of the Brazilian Navy in humanitarian operations: the cases of earthquakes in Haiti and Chile in 2010 - Bianca Gomes Soares Gonçalves de Mendonça; Abdon Baptista de Paula Filho; Adriana Leiras (Production)
Abstract Paper aims Based on the naval logistics doctrine, this paper describes and analyzes the Brazilian Navy's actions and the obstacles encountered in humanitarian operations conducted during the earthquakes in Haiti and Chile, both in 2010. Originality The main contribution is to report the use of Brazilian military personnel in humanitarian operations, with its distinct characteristics, serving as a basis for future works on this theme. Research method The research is qualitative and descriptive with an exploratory objective, based on Brazilian Navy mission reports, the legal doctrines that govern military logistics, and interview with militaries. Main findings The analysis of the reported cases brings lessons that the Naval Force may incorporate into possible future humanitarian operations. Implications for theory and practice The findings can also serve as a reference for a benchmark discussion of military operations in disaster response.